The Fear of Flying: Reflections on Retirement - Jeffrey Zacharakis (Adult Education Research Conference, 2023)
I explore how I have defined adult education through my actions and decisions, how has adult education defined who I am, and how has adult education changed during my career.
Keywords: sociology; philosophy; adult education